Vibrio coralliirubri sp. nov., a new species isolated from mucus of red coral (Corallium rubrum) collected at Procida island, Italy - Poli, Annarita; Romano, Ida; Mastascusa, Vincenza; Buono, Lorena; Orlando, Pierangelo; Nicolaus, Barbara; Leone, Luigi; Hong, Kar Wai; Chan, Kok Gan; Goh, Kian Mau; Pascual, Javier (Springer, 2018)
Strain Corallo1T was isolated from mucus of red coral (Corallium rubrum) at Punta Pizzaco (Procida island, Naples, Italy). It was characterised as a Gram-stain negative, motile, rod-shaped bacterium. Strain Corallo1T was found to show positive responses for cytochrome-c oxidase, catalase, reduction of nitrate and nitrite, β-galactosidase activity and hydrolysis of starch, xylan, peptone, Tween 40, Tween 80 and casein. Strain Corallo1T was found to be mesophilic, neutrophilic to alkalophilic and slightly halophilic. According to analysis of the almost-complete 16S rRNA gene, strain Corallo1T is closely related to Vibrio celticus (100% sequence similarity), Vibrio gigantis (100%), Vibrio crassostreae (99.7%), Vibrio artabrorum (99.7%) and Vibrio pomeroyi (99.6%). MLSA of five housekeeping genes (atpA, pyrH, recA, rpoA and rpoD) was performed to refine the phylogenetic relationships of strain Corallo1T. A draft genome sequence of strain Corallo1T was obtained. The DNA G+C content of this strain was determined to be 44.5 mol %. The major cellular fatty acids of strain Corallo1T are C16:1, n-C16:0 and C18:1, and the major isoprenoid ubiquinone is Q8. ANI indexes, in silico estimations of DDH values and wet lab DDH values demonstrated that strain Corallo1T represents an independent genomospecies. Based on a polyphasic taxonomic characterisation, strain Corallo1T is concluded to represent a novel species of the genus Vibrio, for which the name Vibrio coralliirubri sp. nov. is proposed. The type strain is Corallo1T (= DSM 27495T = CIP 110630T).